2004
DOI: 10.1177/0363546503262644
|View full text |Cite
|
Sign up to set email alerts
|

Anchor Design and Bone Mineral Density Affect the Pull-Out Strength of Suture Anchors in Rotator Cuff Repair

Abstract: Suture anchors should be placed in the proximal-anterior and -middle parts of the greater tuberosity. In the distal parts, biodegradable hook-like anchors should be used with caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
129
4
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(143 citation statements)
references
References 19 publications
(80 reference statements)
6
129
4
4
Order By: Relevance
“…Both biological and mechanical factors influence anchor performance. Many studies have examined the ''bio'' portion of pullout strength by investigating variables such as bone mineral density 21,22,32 ; our study should serve as a counterpart to study mechanical factors while blocking out biological variations by using a consistent test medium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both biological and mechanical factors influence anchor performance. Many studies have examined the ''bio'' portion of pullout strength by investigating variables such as bone mineral density 21,22,32 ; our study should serve as a counterpart to study mechanical factors while blocking out biological variations by using a consistent test medium.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] Pullout strength decreases significantly in osteoporotic bone which has poor bone mineral density. As pullout becomes the dominant mode of failure, anchor design will have an amplified impact on strength.…”
mentioning
confidence: 99%
“…Fixation strength, particularly for bone anchors, depends, in large part on bone quality and device design. In a recent cadaver study of rotator cuff reattachment to the proximal humerus, Tingart et al 6 reported a positive correlation between cortical bone mineral density and the failure force of the suture anchor. We are unaware of any reports on the effect of bone quality on flexor tendon-bone repairs performed using 2 bone anchors.…”
Section: Introductionmentioning
confidence: 99%
“…In einer anderen Kadaverstudie wurde der lokoregionäre Knochendichte-Gehalt im Bereich des Tuberculum majus quantitativ bestimmt [36]. Im Gegensatz zu Meyer et al [29] fand sich hier ein signifikant höherer spongiöser Knochendichte-Gehalt im posteroproximalen verglichen mit dem antero-bzw.…”
Section: Sehneninsertionunclassified
“…medioproximalen Anteil des Tuberculum majus. Allerdings korrelierten die maximalen Ausreißkräfte der verwendeten Fadenankersysteme nicht mit dem lokoregionären spongiösen Knochendichte-Gehalt, sondern zeigten eher eine Abhängigkeit vom lokoregionären kortikalen Knochendichte-Gehalt [36]. Hier ließen sich im anterobzw.…”
Section: Sehneninsertionunclassified